Then the troll heard the squeak - Hawkes, Kevin (New York : Puffin Books, 1992)
Little Miss Terry weaks havoc by jumping on the bedspring at night, until a troll appears to set things aright.
Keywords: Trolls-Fiction; Behavior-Fiction; Stories in rhyme